Color and light - Taylor, Barbara, 1954-; Millard, Peter (New York ; London : Franklin Watts, 1990)
Explains the properties of light which make variation in color possible and suggests projects and experiments to demonstrate such principles.
4.6
3-6
School Library Journal
Booklist
Keywords: Color -- Juvenile literature; Color -- Experiments -- Juvenile literature; Light -- Juvenile literature; Light -- Experiments -- Juvenile literature; Color -- Experiments; Light -- Experiments; Experiments